The Effect of Atmospheric Attributes Inside Restaurants on Social Media Branding - Dewi, Ova Candra; Irma, Donna; Sari, Joice Sandra (Jurnal Teknik Sipil dan Perencanaan, 2020)
This paper explains the most influential facilities in the hospitality industry particularly restaurant in Jakarta. In recent years, many restaurants compete with each other in order to survive the marketing competition. Furthermore, in this digital era, having good branding on social media will be very helpful in the restaurant business. Social media provides the most effective business marketing for the business, due to its speed and accuracy for targeting the desired market segmentation. Perceiving this potential, the restaurant owners try to build good branding in social media in order to construct the market expectations. Consequently, the physical environment as an atmosphere element in a restaurant is critical to strengthen the restaurant branding on social media. It can improve the quality of the atmosphere produced in order to create a satisfying visiting experience. Therefore, when the expected amount of the visitors is reached, they will be driven to perform social media behavior (word of mouth). This study describes the impact of word of mouth by restaurant visitors on social media created by the quality of atmospheric attributes that will effectively affect the overall branding of the restaurant. In this study, the restaurants with good social media reputation under different characteristics and concept in Jakarta have been selected as the case studies. The aim to select them as case studies is to find a common thread of differences. The hypothesis made of this study is that restaurants with harmonious atmospheric attributes will provide a satisfying experience for visitors which will trigger social media behavior in enhance the branding.